Case series to depict the outcomes of commonly available laboratory investigations in molluscum-like skin lesions among HIV positive patients - Pradeep Balasubramanian; Chhakchhuak Laldinthari; Rebecca Lalngaihzuali; C Laltlanzovi; Swagnik Roy; Gracy Laldinmawii; Robert Lalnunpuia; Lalnunsangi Sailo (Wolters Kluwer Medknow Publications, 2023)
Molluscum-like skin lesions in HIV patients can be the presenting feature of the vast array of diseases. Hence, laboratory investigations play a crucial role in making an accurate etiological diagnosis. The studies that discuss the outcomes of commonly performed laboratory tests in molluscum-like lesions in HIV patients are very sparse. Hence, we conducted a study to bridge this literature gap. This study was conducted among four patients with HIV who had molluscum-like skin lesions. Shave biopsy was performed on all the patients and the specimens were sent for potassium hydroxide (KOH) mount/gram stain, fungal culture and histopathological examination. The tissue samples from cases 1, 2, 3 and 4 are mentioned as samples A, B, C and D, respectively. KOH mount showed yeast-like rounded bodies around 6 μm in size in samples A and B. The KOH mount in samples C and D showed septate branching hyphae. KOH mount in sample C also showed large rounded bodies around 35 μm which were identified as molluscum bodies. The histopathology of samples A and B showed features suggestive of talaromycosis whereas the histopathology of samples C and D showed features of molluscum contagiosum. Culture in Sabouraud Dextrose Agar grew T. marneffei in samples A, B and C. The commonly available laboratory tests immensely help in establishing the diagnosis of molluscum-like skin lesions. However, certain nuances in laboratory tests need to be understood lucidly. Studies with larger sample sizes need to be conducted to determine the possible co-infection of poxvirus and T. marneffei, as witnessed in sample C.